Effect of cassava leaf harvesting on a cassava green mite predator in the Democratic Republic of Congo - Tata-Hangy, K.W.; Hanna, R.; Toko, M.; Solo, M. (2004)
Typhlodromallus aripo, a predatory phytoseiid species of the cassava green mite Mononychellus tanajoa was introduced to the Democratic Republic of Congo in 1998. It established easily and spread quickly to other areas from the sites of first release. But its dispersal was constrained by intense consumption and trade of young tender cassava leaves, the natural habitat of the predator. A negative and significant correlation was found between the incidence of the harvest and the plants with T. aripo. Harvesting at 30, 45 and 60 days interval led to population densities of T. aripo for the entire production period of 1.823, 1.972 and 3.675 predators units per plant, respectively. For the check where no harvest was done, population density was 7.242 per plant. Significant differences, (P<0.05; LSD=1.277) were observed between harvests at 30 and 45 days at 60 days T. aripo population density remained low and reached zero in plots harvested every 30 and 45 days interval. There was no significant treatment effect on M. tanajoa damage on the plants, although the density of this pest was significantly higher in plots where harvesting was not done.